2010
DOI: 10.1002/mnfr.200900552
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gastrointestinal digestion of the major peach allergen Pru p 3, a lipid transfer protein: Molecular characterization of the products and assessment of their IgE binding abilities

Abstract: A simulated gastrointestinal digestion has been carried out on purified peach lipid transfer protein, one of the main allergens among the population of the Mediterranean area and the major allergen of peach allergic patients. The percentage of intact protein, after extensive digestion, measured by comparison with a non-digestible peptide analogue used as internal standard, was found to be about one-third of the original protein content. The peptides formed in digested fraction were characterized by means of LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
6
28
0
Order By: Relevance
“…In fact, sensitization to Pru p 3 has been shown to be associated with an increased risk of both, prevalence and severity of food allergies [34]. We found that Api g 2 was highly resistant to simulated gastrointestinal digestion and although the primary sequence contains 19 potential pepsin cleavage sites it displayed an enormous stability comparable to that of Pru p 3 [35,36]. Even upon prolonged proteolysis (48 h of pepsin and 24 h of trypsin/chymotrypsin treatment) intact Api g 2 could be detected.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, sensitization to Pru p 3 has been shown to be associated with an increased risk of both, prevalence and severity of food allergies [34]. We found that Api g 2 was highly resistant to simulated gastrointestinal digestion and although the primary sequence contains 19 potential pepsin cleavage sites it displayed an enormous stability comparable to that of Pru p 3 [35,36]. Even upon prolonged proteolysis (48 h of pepsin and 24 h of trypsin/chymotrypsin treatment) intact Api g 2 could be detected.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, these reactions are frequently more severe than the classic oral allergy syndrome (OAS) expected in food allergy related to sensitization to Bet v 1, the major allergen from birch pollen (43). This could be explained by the fact that ns-LTPs, unlike Bet v 1 homologues, resist to gastroduodenal proteolysis (44,45) and thermal processing (46)(47)(48). However, it should also be kept in mind that in addition to plant-food allergies, sensitization to Can s 3 might also explain cross-reactions to ns-LTP present in various sources such as Hevea latex (49-51), alcoholic beverages such as beer and wine (52,53) and finally also tobacco (Nicotinia tabaccum) (9, 38, 54).…”
Section: Clinical Manifestationsmentioning
confidence: 96%
“…ns-LTP are highly stable structures that resist thermal processing [45,46,47] and gastroduodenal proteolysis [48,49]. Thus, both sensitization and triggering of reactions towards C. sativa might result from various routes of exposure such as inhalation, transdermal and also ingestion (e.g.…”
Section: Discussionmentioning
confidence: 99%